Accelerated aging studies of silicon-rubber based polymeric insulators used for HV transmission lines. (September 2017) - Verma, Alok Ranjan; Reddy, B. Subba
Abstract: Accelerated aging experimental investigations are performed on polymeric insulators which are used for extra high voltage (EHV) and ultra high voltage (UHV) transmission. A newly developed rotating wheel and dip test facility as per std. IEC 62217 is used for the study. The experimental study is conducted with AC stress for 15000 cycles. The specimen insulators used are of 725 mm creepage and treated under different environmental stresses close to the real service life. The present study focuses on the effect of acidic environment during acid rain encountered by the polymeric insulators. The contaminants used for the study are as per standard and practically observed acid rain information. A comparative study is carried out for normal and acidic environmental conditions, some interesting results are observed. Leakage current monitoring and visual observation were conducted at regular intervals. Results show acid treatment is found to be comparatively more severe than the normal treatment. Further Physico-chemical investigation are carried out using Fourier Transform Infrared (FTIR) Spectroscopy and Scanning Electron Microscopy (SEM), Energy dispersive X-ray Analysis (EDAX) and Thermo-Gravimetric Analysis (TGA) which confirm the severity of material degradation of polymeric insulators and corrosion over metal end fittings under acidic environmental condition.